OTENTISITAS PENERAPAN ASURANSI SYARIAH DI INDONESIA - Nanda Siti Hardyanti (Universitas Islam Negeri Sumatera Utara, 2019)
Insurance sharia based on the cooperation, responsibities, guarantees, protection and assistance among groups of participants. Islamic Insurance (takaful) is considered as cooperative or mutual insurance, where members contribute to pay sum of money or premiums to insurance companies. This study aims to find out the application of Islamic insurance in Indonesia after the law namber 40 of 2014 concerning insurance. This type of research is librabry research. Primary data used are law Number 40 of 2014 corcerning insurance, law number 2 of 1992 KUHD and DSN-MUI fatwa. While the secondary data used is other literature in accordance with the research. The results of this study are summarized as follows: (1) Sharia insurance is an effort to help one another among a number of people/parties through investments in asset and/tabarru‟ which periode a pattern of returns to deal with certain risks through an agreement in accordance with sharia, with a risk sharing system. (2) The authenticity of sharia insurance in Indonesia is needed by strengthening all Islamic insurance products to run in accordance with sharia privisions, in this case the sharia supervisiory board is an important part in carrying out strict supervision of the activities of sharia insurance institutions. Islamic insurance is a solution to answer Muslim needs for the importance of future planning with halal transactions.